ANALYSIS ON THE FACTORS AFFECTING CAPITAL STRUCTURE ON FOOD AND BEVERAGE COMPANIES IN IDX - Rani Milansari; Endang Masitoh; Purnama Siddi (Universitas Airlangga, 2020)
Capital structure is related with company funding. This study aims to examine and analyze the factors that influence the capital structure of food and beverage companies listed on the Indonesia Stock Exchange. The population in this study amounted to 26 companies and a sample of 40 companies was obtained using purposive sampling technique. This study uses secondary data for the period 2015 – 2018. The data analysis used is multiple linear regression analysis. The results showed that the current ratio and firm size had an effect on capital structure, while return on assets, asset structure and sales growth had no effect on capital structure. The results of the study are expected to be used as consideration for the management in determining the company's funding sources.